Validation of Indonesian Version of Telehealth Usability Questionnaire (TUQ) - Gilbert Sterling Octavius; Theo Audi Yanto (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2023)
Introduction: Indonesia is the 4th most populous country globally, with 250 million people across 17.508 islands. Despite its strong economic growth, the disparity in poverty increases as medical care costs shoot up. With inadequate medical care worker-to-patient ratio, telehealth is an alternative to providing healthcare in rural areas with similar or even better satisfaction rates. The lack of a standardized questionnaire in the Indonesian language encouraged the authors to validate Telehealth Usability Questionnaire (TUQ) in the Indonesian language. Methods: A cross-sectional study via the e-survey method was done from 17th to 31st of July 2020, while telehealth usability questionnaires were translated and adapted according to WHO protocol. The inclusion criteria were telemedicine users above 18 years old who had at least used telemedicine once in the past six months. Exclusion criteria included minors who completed the questionnaire. Results: A total of 102 data were obtained, comprising 73.5% female. The overall alpha coefficient was 0.958. The Kaiser– Meyer–Olkin (KMO) sampling test was satisfactory (KMO = 0.926), and the Bartlett test of sphericity was significant (Chisquare = 1835.043; df = 210; p < 0.001). Ease of use and learnability had the highest Cronbach’s alpha coefficient (0.907), while reliability had the lowest Cronbach’s alpha coefficient (0.794). Conclusion: In conclusion, this paper presents TUQ in the Indonesian language, which had not been done before. This set of questions will help assess the usability of the expanding number of telehealth programs available in Indonesia and allow comparisons to determine which features make them more acceptable to users.